Literatur Riview dan Metodologi Ilmu Pengetahuan Khusus - Fatimah, Siti; Zen, Najmatul Haya; Fitrisia, Azmi (Innovative: Journal Of Social Science Research, 2025)
This study explores the methodology of specific scientific knowledge as an approach to understanding social and cultural phenomena in-depth. A qualitative approach was employed using a literature study method involving literature reviews and document analysis. Various methods, such as observation, interviews, document analysis, biographies, and content analysis, were utilized to produce valid and accountable knowledge. Data analysis was conducted through theme categorization and triangulation to ensure the validity and reliability of findings. The results indicate that the specific scientific methodology not only provides a systematic framework for scientific research but also enables a comprehensive and in-depth understanding of social phenomena. By employing complementary methods, this study successfully identifies the significant roles of each method in collecting valid and systematic data.